Visual FoxPro : for beginners - Madrid, Evangeline W. (Mandaluyong City : Hyperbit COmputer System, 2001)
Visual FoxPro is the object-oriented database management system that gives the user speed, power, flexibility, and provides object and event models that help the user create and modify application faster, create automation servers that can be deployed locally or remotely.
Includes bibliographical references.
System requirements: Pentium-class processor; Windows 98/NT 4.0 with Service Pack 6 or later, Windows 2000 with Service Pack 1 or later operating system.
Keywords: Database management -- Software